A case of missed thoracic fracture masquerading as intra-abdominal injury - Amin O,; Nik Azlan Nik Muhamad,; Afliza AB, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Altered mental status in the setting of polytrauma poses a challenge to the emergency team managing the patient. The tendency to miss positive findings in these circumstances increases several folds due to multiple factors such as depressed mental status/intoxication, presence of distracting injuries and concurrent life-threatening injuries that require more urgent attention. In view of this, NEXUS (National Emergency X-Radiography Utilization Study) criteria of clearing the cervical spine was adopted and used worldwide. Consensus on clearance of the other parts of spine is still lacking. This case reports highlights the findings in a 18-yrs-old male who presented with altered mental status, facial pain and abrasion, following a motor vehicle accident. Facial bone fracture was diagnosed and he was discharged. Three days later, he came with severe epigastric pain. Tenderness on palpation was noted at the spine and Computed Tomography (CT) scan was done. Multiple thoracic vertebra fractures were seen. As a conclusion, thorough primary and secondary survey should be done in patients who have regained full consciousness prior to discharge in order to avoid overlooking other serious injuries.